Leadership succession in Zimbabwe’s pentecostal churches: the case of Zimbabwe Assemblies of God Africa (ZAOGA) and Apostolic Faith Mission in Zimbabwe (AFM) - Nhumburudzi, Loshick; Kurebwa, Jeffrey (Global Journals, 2018)
This study sought to understand the leadership succession issues in Pentecostal churches in Zimbabwe, focusing on ZAOGA and AFM churches. The research compared how the two largest Pentecostal churches in Zimbabwe apply leadership principles in assuring peaceful continuity of their churches through leadership succession. Pentecostalism is a very strong Christian fundamental movement and an extreme of Protestantism. Qualitative methodology was used in the study. Key informant and semi structured interviews were used to collect data. This study found out that Pentecostal founders and leaders did not want to release power and control of their churches and wanted to die in office. In most cases their deaths leaves a power vacuum which is difficult to fill due to incapacity. This has in most cases led to splits and fights among family members and other church leaders.
Keywords: Leadership succession; Pentecostalism; Founder; Leader.